Knowledge of Novice Drivers about Providing First Aid to Victims of a Traffic Accident - Rastauskaitė, Miglė; Paulikienė, Simona (Slauga. Mokslas ir praktika, 2025)
Loss of health due to road injuries is a major global problem. According to the World Health Organisation (WHO), around 1.19 million people are killed, and tens of millions suffer injuries each year in road accidents, many of which are severe and lead to permanent disability. Lithuania is no exception as our country continues to have high statistics on road accidents, which is one of the main external causes of death and serious injuries. According to the legal documents of the Republic of Lithuania, drivers involved in a traffic accident, including novice drivers, are obliged to provide first aid. Proper first aid can be a determining factor as it can save the victim’s life. It is therefore extremely important that road users learn first aid and then improve their knowledge so that they can use it effectively to help victims in the event of an accident.Study object. The aim of the study was to assess novice drivers’ knowledge of first aid for road accident victims. A quantitative study was carried out between November 2024 and February 2025 by using the questionnaire survey method. The questionnaire was placed on the Google Forms platform and, with the permission of the administrators, distributed on the Facebook groups: ‘Regitra Examinations. All about licences, driving forum, Ket rules’, ‘Regitra Examinations’. The sample consisted of 92 novice drivers with no more than two years of driving experience and no professional medical training. The age of the subjects ranged from 22 to 54 years old, with the majority of the drivers participating in the study being under 24 years old.Survey results. The results of the survey showed that the distribution of first aid knowledge among learner drivers varies. The average correct knowledge related to initial resuscitation scored 57.9%, knowledge related to injuries yielded 53.6% correct answers, and knowledge related to the required first aid actions was measured as 71.2%. More than half of the respondents were found to possess knowledge of the correct technique for performing resuscitation, while only less than one-fifth lacked knowledge of the principles of first aid in the face of danger. Although the majority of novice drivers have a good knowledge of how to provide correct first aid for fractures, knowledge of first aid for spinal injuries was found to be insufficient. The results of the study suggest that novice drivers’ knowledge of initial resuscitation and first aid for people with various injuries is generally perceived as poor.
Keywords: first aid; traffic accident; novice drivers